Calcinosis Cutis on Vulgar Wart. Report of a Case - Francisco, Javier Torres-Gómez (Journal of Etiological Diagnosis, 2022)
Verruca vulgaris is a very common lesion, of viral etiology, benign clinical behavior and different types of simple treatments. Its epidemiological, morphological, histological and therapeutic study has been sufficiently reflected in the literature. We present a peculiar clinical case in which calcium deposits developed on a common wart without any alterations in its metabolism being observed in the analytical studies carried out (calcinosis cutis). A 9-year-old male patient attended the dermatology service due to an excrescent keratotic lesion of recent appearance and rapid growth. We have conducted an unsucessful bibliographic search of this relationship, possibly because these have not been communicated because it is simply a morphological finding with no clinical significance.
Keywords: Verruca vulgaris. Calcinosis cutis. Knee.